Clinical Anatomy of the Inferior Alveolar Nerve Block - Benjamin Werner; Jennifer Brueckner-Collins; Robert Acland (Association of American Medical Colleges, 2012)
Abstract Local oral anesthesia is a key component of most dental treatments. A solid understanding of the anatomical basis for administering anesthetic injections correctly is an important component of any dental curriculum (Henzi et al., 2006). Learning the appropriate techniques for delivering effective anesthesia is complex and it is often difficult for students to transfer their conceptual knowledge of anatomy to the first injection on a patient (Brand et al, 2008). Many dental students feel insufficiently prepared for administering their first injection of local oral anesthesia in a patient (Brand et al., 2010). Knowledge of anatomy is a commonly cited area in which students feel underprepared going into their clinical training. In fact, 19% of credentialed dentists report that administering local oral anesthesia causes them distress (Simon et al., 2005). Jenkins and Spackman (1994) described an anatomy program in which second year dental students were exposed to both didactic and laboratory sessions to help them apply their gross anatomy knowledge to anesthetic techniques in the clinic. Second year dental students were instructed to maintain visualization of the needle tip while doing their dissection. They utilized traditionally preserved cadaveric specimens, which are different than the tissue encountered in the clinic, but the authors concluded that experience with depth and angle of injection and bone contact was nonetheless valuable to the student. The present proposal builds upon the work of Jenkins and Spackman in two ways: 1) by using fresh tissue, which more closely approximates the appearance of a live patient's oral mucosal landmarks and 2) by digitally recording an instructional demonstration of the dentist's approach to the most commonly administered mandibular block (inferior alveolar) in high definition and incorporating these clips into an easily navigable multimedia program. The purpose of this instructional video is to review the clinical anatomy of the inferior alveolar nerve block, with emphasis on key intraoral landmarks. This product has been reviewed and evaluated by third year dental students from the Class of 2013 at the University of Louisville. Students recommended that the product be incorporated into both the first year head and neck anatomy course as well as the second year anesthesia course. Students commented that the anatomical views and dissections provided were unique to any material in their standard curriculum. They also cited as strengths of the program the narration, summary and overview, and organization.